The impact of professional orientations on officers’ supervision behaviors in juvenile and adult community corrections: a multi-agency analysis - Bolin, Riane M. (Journal of crime and justice, 2024)
Early scholarship on community corrections officers suggested that officers’ perceptions of their professional role influences how they carry out supervision. While some research has supported this contention, the studies examining the relationship have provided minimal attention to juvenile probation and parole, rarely considered actual as well as intended supervision behaviors, and analyzed samples with limited generalizability. The present study sought to fill this gap. Data were collected through the use of an online questionnaire from a sample of juvenile and adult probation and parole officers employed in seven different agencies in five states during spring 2015. The study found client type to be a significant predictor of both officer actual and intended behaviors, with juvenile PPOs preferring more frequent surveillance techniques and less frequent rewards for probationer progress toward goals. Professional orientation was also a significant predict of both types of behavior. Implications of these findings are discussed.